Digital devices for teaching cardiac auscultation - a randomized pilot study. Issue 1 (1st January 2018) - Legget, Malcolm E.; Toh, MeiYen; Meintjes, Andries; Fitzsimons, Sarah; Gamble, Greg; Doughty, Robert N.
ABSTRACT: Background : Competent cardiac auscultation is a declining skill. Digital stethoscopes and hand-held echocardiography (HHE) are modern devices which may improve the accuracy of heart murmur recognition and diagnosis. Their incremental value compared to conventional examination has not been evaluated in depth. Objectives : Our aim was to quantify the utility of digital stethoscopes and HHE as teaching aids to improve medical students' diagnostic accuracy in the evaluation of heart murmurs using a novel clinically weighted scoring system. Design : This pilot study involved eight medical students and eight patients with heart murmurs. Four patients were examined at 2 sessions, 1 week apart. Medical students were randomised into two groups: the 'intervention group' examined patients with a standard and digital stethoscope, and then received demonstration of the valvular lesion with HHE to illustrate the diagnosis. The 'control group' used a standard stethoscope only and were taught using traditional methods. Students' scores were compared to a 'gold standard' derived from a consensus of auscultation findings of three cardiologists. Results : Overall the mean percent correct of total possible score was 65.4% (SD8.4). Using a mixed models ANOVA approach to repeated measures, the mean [95% CI] increase from training to validation period for the control group was 2.5% [−11.5, 16.5] P (Tukey) = 0.95 and 15.8% [1.7, 29.8] P (Tukey) = 0.027 for the intervention group. Between the validation and training sessions for both groups, there was an increase of 9.1% [1.82, 16.4] in scores ( p = 0.018). The mean [95% CI] difference in scores of the control and intervention groups was 1.9% [−5.4, 9.2] ( p = 0.59). The Cohen's effect size estimate was 0.9. Conclusion : Digital stethoscopes and hand-held echo may be useful devices for teaching cardiac auscultation. This pilot study provides a novel study design, a heart murmur grading system, and data that will help develop definitive studies to assess new teaching techniques for cardiac auscultation using digital technology.